The Impact of Intellectual Capital on Earning Quality Experimental study on a sample of industrial companies listed on the Amman Stock Exchange during the period 2015 –2021 - zeghoud, teber (Journal of Research in Finance and Accounting, 2023)
This study aimed to test the impact of intellectual capital on earning quality of a sample of 18 industrial companies listed on the Amman Stock Exchange in Jordan during the period 2015-2021. to achieve this objective, the study was based on the construction of Panel Data Model, which included earning quality as a dependent variable, And intellectual capital (human capital, structural capital and relational capital) as an independent variable, in addition to some other variables affecting that relationship. The study found that there is an positive relationship between human capital efficiency and the earning quality in industrial companies listed on the Amman Stock Exchange, and the negative relationship between the structural capital efficiency and earning quality in industrial companies listed on the Amman Stock Exchange.